Exploring opportunities for sustainable expansion of groundwater use in the lowlands of Laos - International Water Management Institute; CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2019)
The lowlands of Laos support around 70% of the population, have by far the greatest potential for expansion of market-oriented agriculture. The lowlands are also prone to drought and regularly face water shortages. Groundwater, which is available year-round offers a potential solution. Communities situated far from reliable surface water supplies could benefit greatly if groundwater use could be sustainably expanded, particularly for irrigation by smallholders. The national agricultural development strategy recognizes the lowlands as a priority for expansion of livelihood enhancing actions, including diversified cropping. A commitment to enhancing climate resilience in drought-prone areas means that irrigation could evolve as a major user of groundwater. However, information on the aquifer systems is extremely limited, which greatly constrains proper planning and development. Another limitation is the groundwater pumping costs, particularly for diesel pumps. Earlier research revealed substantial promise for groundwater to enhance livelihoods in rural Laos however further work is needed to better understand how groundwater irrigation can support agricultural development.